Improving critical thinking and metacognitive skills through the discovery learning model assisted by practicum for high school students - Pratama, Aditya; Sari, Tasya Novian Indah; Istiqomah, Nurul; Widiyanti, Eka Riana; Kusniati, Yen (Biosfer: Jurnal Pendidikan Biologi, 2024)
Metacognitive abilities and critical thinking support the success of learning biology, so these skills need to be empowered. The purpose of this study is to determine the effectiveness of the practicum-based discovery learning model to improve critical and metacognitive thinking skills in digestive system material. The research method is a quasi-experimental research with a one-grub pretest-posttest design. The research was conducted from November to December 2022 at SMA Negeri 9. The research was carried out from November to December 2022 at one of the high schools in Mataram City. The research population was 98 students of class XI Science. The research sampling technique is a purposive sampling technique. The data collection technique used a test technique, namely 9 critical thinking essay questions and MAI. The instruments used in this study were the ability to think critically about the digestive system with several questions and the MAI instrument. The data analysis technique uses inferential statistics using the Paired Sample T-Test Assisted by SPSS IBM 27 software. The results of the study show that with an alpha of 5%, the practicum-based discovery learning model is effective for increasing critical thinking skills and metacognitive abilities. The average pre-test of critical thinking skills on the digestive system material was 54.0333 and the post-test was 75.8667. While the average pre-test of metacognitive abilities is 73.37 and the post-test of metacognitive abilities is 76.93 The application of the practicum-based discovery learning model effectively improves students' critical thinking and metacognitive skills with an alpha significance level of 5%.